Choice regularities of antihypertensive therapy regimens of primary open-angle glaucoma in conditions of real clinical practice - Z.M. Nagornova; A.V. Seleznev; P.Ch. Zavadskiy; A.V. Kuroyedov (РМЖ "Клиническая офтальмология")
Z.M. Nagornova1, A.V. Seleznev1, P.Ch. Zavadsky2, A.V. Kuroyedov3,4 1 Ivanovo State Medical Academy, Russian Federation 2 High-tech Cataract Treatment Center «New Vision», Minsk, Republic of Belarus 3 Central Military Clinical Hospital named after P.V. Mandryka, Moscow, Russian Federation 4 Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to study effectiveness of different regimens of primary open-angle glaucoma (POAG) therapy, choice and change algorithms of ophthalmic treatment components in conditions of real clinical practice. Patients and Methods: results of 398 patients (641 eyes) with different stages of POAG, diagnosed at least 6 months ago, were included in this study. At the time of enrollment in the study, a stage of the disease was verified according to current classification of glaucoma with intraocular pressure (IOP) measurement, analysis of morphometric and functional indices. Results: a mean level of IOP (all stages of the disease) at the time of glaucoma diagnosis was 28.00 (26.00; 30.00) mm Hg. It was established that a number of patients with IOP compensation is inversely proportional to a stage of the disease. All patients with the glaucoma (641 eyes) had 44 different regimens (therapy, lasers, surgery). IOP levels were analyzed in the patients with different stages of POAG who received these different regimens of therapy. Those patients in whom an advanced stage of the disease was diagnosed had significantly higher IOP at the time of diagnosis than patients with a second and first stage of the disease. An analysis of dependence of therapy regimen content on glaucoma history duration in the different stages of POAG was carried out, and the most “popular” regimens used were established. Conclusion: IOP level at the time of POAG diagnostics can determine a stage of the disease and serve as a prognostic sign of a disease course. To achieve a target IOP is possible at an early stage of the glaucoma in 95.86% of cases, at a moderate and advanced — in 74.14% and 35.95% of cases, respectively. There is a tendency to be chosen as a starting regimen for the early glaucoma of monotherapy with beta-blockers, while prostaglandin analogues are prescribed for duration of the disease for more than a year. With higher-level stages of the glaucoma, combinations of drugs and penetrating glaucoma surgery prevail. Key words: glaucoma, intraocular pressure, beta-adrenoblockers, prostaglandin analogues, combination therapy, therapy regimens. For citation: Nagornova Z.M., Seleznev A.V., Zavadsky P.Ch., Kuroyedov A.V. Choice regularities of antihypertensive therapy regimens of primary open-angle glaucoma in conditions of real clinical practice. RMJ “Clinical ophthalmology”. 2018;3:116–123.